Factors Affecting the Implementation of Electronic Antiretroviral Therapy Adherence Monitoring and Associated Interventions for Routine HIV Care in Uganda: Qualitative Study - Haberer, Jessica E; Garrison, Lindsey; Tumuhairwe, John Bosco; Baijuka, Robert; Tindimwebwa, Edna; Tinkamanyire, James; Burns, Bridget F; Asiimwe, Stephen (JMIR Publications, 2020)
BackgroundHigh, sustained adherence to HIV antiretroviral therapy (ART) is critical for achieving viral suppression, which in turn leads to important individual health benefits and reduced secondary viral transmission. Electronic adherence monitors record a date-and-time stamp with each opening as a proxy for pill-taking behavior. These monitors can be combined with interventions (eg, data-informed adherence counseling, SMS-based adherence support, and/or alarms) and have been shown to improve adherence in multiple settings. Their use, however, has largely been limited to the research context. ObjectiveThe goal of the research was to use the Consolidated Framework for Implementation Research (CFIR) to understand factors relevant for implementing a low-cost electronic adherence monitor and associated interventions for routine HIV clinical care in Uganda. MethodsWe conducted in-depth qualitative interviews with health care administrators, clinicians, and ART clients about likes and dislikes of the features and functions of electronic adherence monitors and associated interventions, their potential to influence HIV care, suggestions on how to measure their value, and recommendations for their use in routine care. We used an inductive, content analysis approach to understand participant perspectives, identifying aspects of CFIR most relevant to technology implementation in this setting. ResultsWe interviewed 34 health care administrators/clinicians and 15 ART clients. Participants largely saw the monitors and associated interventions as favorable and beneficial for supporting adherence and improving clinical outcomes through efficient, differentiated care. Relevant outside factors included structural determinants of health, international norms around supporting adherence, and limited funding that necessitates careful assessment of costs and benefits. Within the clinic, the adherence data were felt likely to improve the quality of counseling and thereby morale, as well as increase the efficiency of care delivery. Existing infrastructure and care expenditures and the need for proper training were other noted considerations. At the individual level, the desire for good health and a welcomed pressure to adhere favored uptake of the monitors, although some participants were concerned with clients not using the monitors as planned and the influence of poverty, stigma, and need for privacy. Finally, participants felt that decisions around the implementation process would have to come from the Ministry of Health and other funders and would be influenced by sustainability of the technology and the target population for its use. Coordination across the health care system would be important for implementation. ConclusionsLow-cost electronic adherence monitoring combined with data-informed counseling, SMS-based support, and/or alarms have potential for use in routine HIV care in Uganda. Key metrics of successful implementation will include their impact on efficiency of care delivery and clinical outcomes with careful attention paid to factors such as stigma and cost. Further theory-driven implementation science efforts will be needed to move promising technology from research into clinical care. Trial RegistrationClinicalTrials.gov NCT03825952; https://clinicaltrials.gov/ct2/show/NCT03825952